1985
DOI: 10.1161/01.cir.72.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in symptoms and exercise tolerance by metoprolol in patients with dilated cardiomyopathy: a double-blind, randomized, placebo-controlled trial.

Abstract: It has been suspected that the increased sympathetic activity seen in patients with chronic congestive heart failure from dilated cardiomyopathy may be harmful. We therefore tested the long-term effect of metoprolol on eight patients in a double-blind, randomized protocol and 12 patients in an unblinded, crossover protocol who were treated for 12 months (range 10 to 24), and compared them with 16 similar subjects who were treated with placebo for 10 months (range 6 to 12) in a doubleblind, randomized protocol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(116 citation statements)
references
References 25 publications
3
110
0
2
Order By: Relevance
“…Many studies, including prospective double-blind placebo-controlled trials, have reported that -blockers contributed to the improvement of survival or symptoms in patients with DCM. [8][9][10][11][12][13]17 In our study, the survival curve of patients treated with -blockers began to separate from that of patients treated without -blockers at the 10th month. The late expression of the -blocking effect may be due in part to the gradual increase of the daily dose of metoprolol, which we carefully employed to avoid acute exacerbation of pump failure because most patients were treated in an outpatient clinic.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies, including prospective double-blind placebo-controlled trials, have reported that -blockers contributed to the improvement of survival or symptoms in patients with DCM. [8][9][10][11][12][13]17 In our study, the survival curve of patients treated with -blockers began to separate from that of patients treated without -blockers at the 10th month. The late expression of the -blocking effect may be due in part to the gradual increase of the daily dose of metoprolol, which we carefully employed to avoid acute exacerbation of pump failure because most patients were treated in an outpatient clinic.…”
Section: Discussionmentioning
confidence: 94%
“…DBA/2 mice were inoculated with the virus and were given carteolol at a dose of 1 (n=12) or 10 mg/kg (n=16), or distilled water (n =27) subcutaneously daily starting on day 14 after inoculation. Mice were killed on day 28.…”
Section: Experimental Infection and Treatmentmentioning
confidence: 99%
“…1A). This might be because of increased numbers of myocardial ␤-adrenergic receptors, as observed during long-term ␤-adrenergic blocker therapy, 7 8 resulting in increased exercise capacity 10 and an exaggerated response to exogenous catecholamines such as dobutamine. 8 As endogenous catecholamines increase during acute isovolaemic haemodilution 16 17 and this is considered an important mechanism for the increase in cardiac index, 1 it is conceivable that after long-term oral ␤-blocker therapy patients may respond with a greater increase in cardiac index compared with non-␤-blocked patients.…”
Section: Discussionmentioning
confidence: 99%